2010
DOI: 10.1039/b923246j
|View full text |Cite
|
Sign up to set email alerts
|

“Cosmetic electrochemistry”: the facile production of graphite microelectrode ensembles

Abstract: The facile and rapid production of microelectrode ensembles is shown to be possible using off-the-shelf cosmetic products and is exemplified with the electrochemical sensing of a toxic metal offering a novel fabrication methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The surface of bare SPCE (Fig. 4A) is composed of flakes of graphite with various diameters, all in the micrometer range, which is in accordance with previously published results (Choudhry et al, 2010a;Gornall et al, 2009;Kadara et al, 2009a). From the comparison of bare and spray modified SPCE (data not shown), it can be concluded that the polymer present in the cosmetic spray filled in the gaps and reduced the amount of accessible graphite, which accounts for the reduction in the voltammetric peak current when the spray modification time was increased (Fig.…”
Section: Spray Modified and Aniline Polymerized Spcesupporting
confidence: 79%
See 4 more Smart Citations
“…The surface of bare SPCE (Fig. 4A) is composed of flakes of graphite with various diameters, all in the micrometer range, which is in accordance with previously published results (Choudhry et al, 2010a;Gornall et al, 2009;Kadara et al, 2009a). From the comparison of bare and spray modified SPCE (data not shown), it can be concluded that the polymer present in the cosmetic spray filled in the gaps and reduced the amount of accessible graphite, which accounts for the reduction in the voltammetric peak current when the spray modification time was increased (Fig.…”
Section: Spray Modified and Aniline Polymerized Spcesupporting
confidence: 79%
“…Cyclic voltammograms at 0.005 V s ( Fig. 1B) revealed the microelectrode behavior as presented in other studies (Choudhry et al, 2010a;Huang et al, 2009;Kadara et al, 2009b). Increasing the spray time had a significant reduction effect on the peak intensity and the peak-to-peak separation revealing that the cosmetic spray reduced the amount of accessible graphite ( Figs.…”
Section: Spray Modified Spcementioning
confidence: 57%
See 3 more Smart Citations